Đánh giá mức độ ô nhiễm các nguồn nước ngầm khu vực Ninh Hòa, tỉnh Khánh Hòa - Tú, Vũ Lê; Watkins, Ron (Vietnam Journal of Earth Sciences, 2007)
Estimating the pollution potential of ground water sources in Ninh Hoa area, Khanh Hoa province